Psychological bases for teaching elementary schoolchildren simple experimentation - E.V. Chudinova; I.A. Shishkina (Психологическая наука и образование)
Context and relevance. Experimentation as a general way of acting and thinking provides the basis for understanding all the natural sciences. That is why the ability to experiment is considered an important outcome of modern primary education. However, the conditions of effective training of junior schoolchildren in experimentation and the age possibilities of mastering this method of action have not been identified, which determines the relevance of this study. Objective. To describe the peculiarities of the simplest experimentation as a way of action and to characterise the age possibilities and conditions of mastering this way by junior schoolchildren through the design of experimental teaching. Hypothesis. Planning of the simplest experiments is included in the age possibilities of junior schoolchildren. The effectiveness of mastering the mode of action depends on the independence of pupils in discovering the need to control the conditions of the experiment. Methods and materials. Logical and logical-psychological analysis of the simplest experimentation. Formative experiment (analysis of video recordings). Comparative survey: an experimental class (27 pupils, 14 girls and 13 boys), which was taught experimentation in accordance with the principles of the D.B. Elkonin-V.V. Davydov system, and three control classes (two second classes, a total of 50 pupils, including 20 girls and 30 boys, and one fourth class, 25 pupils, including 10 girls and 15 boys), taught according to the traditional method. Results. Second grade students who were taught experimentation through setting and solving a learning problem demonstrated an understanding of the differences between experimental and control conditions and planned experiments at the level of fourth graders taught using the traditional curriculum (Mann-Whitney U-criterion, p = 0,117). Analysis of lesson videos and control measurements revealed dynamics and a key difficulty in mastering experimentation related to the need to simultaneously perform two opposite actions – opposing and equalising conditions for experimental and control subjects. Conclusions. It is shown that the simplest experimentation is accessible for mastering by junior schoolchildren, but the essential condition of mastering is the pupils' independent discovery of the necessity of controlling the conditions of experience. It is recommended to strengthen the activity character of teaching experimentation in traditional primary schools in order to achieve this important meta-subject result.